Rasionalitas Peresepan Obat Batuk Ekspektoran Dan Antitusif Di Apotek Jati Medika Periode Oktober-Desember 2012 - Uswatun Hasanah Linnisaa; Susi Endra Wati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2013)
Abstrasi: The pattern of prescribing by doctors in Indonesia are still many who do not meet the standards of rationality treatment. This could be due to lack of knowledge about medicine and doctors due to the limitations of the existing drug supply and availability of drugs at the pharmacy information to physicians. This prescription rationality includes precision dosage, drug, patients, and indications. Besides the standard rationality in the prescription, the doctor also pay less attention to the interaction of the drug to other drugs. This study included non-experimental research carried out by collecting prescription data obtained by reading the recipes patients suffering from cough in pharmacy Teak Medika months from October to December 2012. Analysis of the results was done by determining whether the prescribing pattern already meet the standards of rationality.Keyword: Cough Expectorants, rationality PrescribingÂ Abstrasi: Pola peresepan oleh dokter di Indonesia masih banyak yang belum memenuhi standar rasionalitas pengobatan. Hal ini bisa disebabkan kurangnya pengetahuan dokter tentang obat dan disebabkan keterbatasan persediaan obat yang ada dan informasi ketersediaan obat di apotek kepada dokter. Rasionalitas peresepan ini meliputi ketepatan dosis, obat, pasien, dan indikasi. Selain standar rasionalitas dalam peresepan, dokter juga kurang memperhatikan interaksi obat terhadap obat lain.Penelitian ini termasuk penelitian non eksperimental dilakukan dengan mengumpulkan data resep yang diperoleh dengan membaca resep pasien yang menderita batuk di Apotek Jati Medika bulan Oktober-Desember 2012. Analisis hasil dilakukan dengan menentukan apakah pola peresepan sudah memenuhi standar kerasionalan.Kata Kunci: Obat Batuk Ekspektoran, Rasionalitas Peresepan